Progress in plasmonic solar cell efficiency improvement: A status review. (November 2016) - Mandal, P.; Sharma, S.
Abstract: Solar cell efficiency improvement has been one of the major concerns to realize ultimately the cost effective efficient solar cells. Among various ways to improve solar cell efficiency, plasmonic light trapping mechanism has been found to be of immense interests recently. The mechanism of strong scattering into the active materials and guiding of light at the excitation of plasmons at the metal-semiconductor interface play significant role for better photon harvesting. The present review concentrates on the recent advances on the application of plasmonics in inorganic semiconductor solar cell efficiency improvements. Various research groups active in this field have employed various metal nanostructures on to the surface of solar cells to achieve higher efficiency. This review partially also concentrates on surface nanopatterning of solar cells with nonmetallic dielectrics. Finally, a brief account on the dye-sensitized solar cell is presented to show the potential of plasmonics in solar cell research.